CONSTRAINTS IN ADOPTION OF SCIENTIFIC FISH FARMING IN TELANGANA STATE - A. MEENA; V. RAJANI, D. UTTEJ, A. SAILAJA, B. SAVITHA, G. E. CH. VIDYA SAGAR (The Journal of Research, PJTSAU, 2023)
Fishery in India is a very important economic activity and a flourishing sector with varied resources and potentials. India is the 3rd largest fish producing and 2nd largest aquaculture nation in the world after China. Fisheries and aquaculture remain an important source of food, nutrition, employment and income for millions, especially the rural populations. In fact, the sector provides livelihood to about 25 million fishers and fish farmers at the primary level and twice the number along the value chain.